A label-free electrochemical aptasensor for the detection of kanamycin in milk. Issue 5 (28th January 2015) - Zhou, Nandi; Luo, Jibao; Zhang, Juan; You, Yuanding; Tian, Yaping
Abstract : Kanamycin is detected based on the conformational change of the aptamer attached to the electrode surface and the corresponding SWV current change in [Fe(CN)6 ] 3−/4− solution. Abstract : Kanamycin is a widely used aminoglycoside antibiotic, and residual kanamycin in animal-derived food causes serious side effects. Herein, a simple aptamer-based assay is proposed for the label-free electrochemical detection of kanamycin. A 5′-SH-modified kanamycin-specific aptamer was self-assembled on the surface of a gold electrode through Au–S chemistry. Upon binding to kanamycin, the conformation of the aptamer changes and its coverage of the electrode surface increases, owing to the formation of a stem-loop structure in the complex. As a result, the electron transfer resistance between the solution species and the electrode is increased. Using [Fe(CN)6 ] 3−/4− as a probe, the square wave voltammetry (SWV) current response was utilised to determine the concentration of kanamycin. The detection range of the aptasensor was found to be 10–2000 nM, indicating a high sensitivity and a broad detection range. The specificity of detection was also determined. Furthermore, the assay was successfully employed in the detection of kanamycin in milk samples, with a similar response range and detection limit.